Stateczność Wstępnie Sprężonego Pasma Sprężystego - Z. Wesołoski; J. Mączyński (Engineering Transactions, 1975)
The problem of stability of an elastic system subjected to large deformations has been considered in a number of papers. A complete literature of the subject is given in the monograph [1]. One group of relevant work was concerned with an initially pre-stressed cylinder. The pre-stressed state was obtained by bending of a cylinder section until the edges are met and joined together. The so obtained cylinder does not have a natural configuration as a whole. The present paper an initially pre-stressed strip is considered which also does not possessas a whole a natural configuration. The initial pre-stressed might result from a production process (for example vulcanization) or it may be intentionally introduced by means of mechanical, physical or chemical processes.